PEMBERDAYAAN EKONOMI MELALUI WORKSHOP INTEGRATED MARKETING BAGI IBU-IBU PKK: Studi Kasus Pada Usaha Gelang Manik-Manik - Nur , Anisah; Afif, Al Ghozy Haidar (COMVICE: Journal Of Community Service, 2025)
A form of community service with a focus on increasing the economic capacity of Family Welfare and Empowerment through bead-making skills. The fostered partners, who have creative potential in making beads, face obstacles in product packaging, budget management, and digital marketing. To overcome these problems, our community service team applies intensive training and mentoring methods. The implementation of activities includes training in attractive and functional packaging design, preparation of efficient production budgets, and utilization of social media and e-commerce platforms for product marketing. The results of the coaching show a significant increase in the quality of more attractive product packaging (75% increase in quality), understanding of financial management (60% increase based on evaluation results), and increasing market reach through digital marketing (40% increase in online sales based on sales data). The follow-up plan that will be carried out is ongoing mentoring in developing product designs and strengthening digital marketing strategies to ensure the sustainability of partner businesses